2015
DOI: 10.1055/s-0035-1546197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hautriwaic Acid Isolated from Dodonaea viscosa in a Model of Kaolin/Carrageenan-Induced Monoarthritis

Abstract: In the present work, the antiarthritic activity of hautriwaic acid is reported. This ent-clerodane diterpene isolated from Dodonaea viscosa was evaluated in mice using a kaolin/carrageenan-induced monoarthritis model. The inflammation observed in the joint (knee) on days 1-8 ranged from 50-70 %. After 10 days of treatment with different doses of hautriwaic acid (5, 10, 20 mg/kg), a decrease in knee inflammation was detected. This recovery was observed with both reference drugs, methotrexate (1 mg/kg) and diclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The administration of this substance resulted in localized inflammation associated with the production of a number of mediators such as TNF-α and IL-1β [22]. In a study in our laboratory, it has been shown that the intra-articular administration of carrageenan, as an experimental procedure, induced an important local increment of TNF-α and IL-1β [23]. It has been demonstrated that TNF-α induces cartilage and bone degradation, and the penetration of lymphocytes, macrophages, and neutrophils to the joint cavity.…”
Section: Discussionmentioning
confidence: 97%
“…The administration of this substance resulted in localized inflammation associated with the production of a number of mediators such as TNF-α and IL-1β [22]. In a study in our laboratory, it has been shown that the intra-articular administration of carrageenan, as an experimental procedure, induced an important local increment of TNF-α and IL-1β [23]. It has been demonstrated that TNF-α induces cartilage and bone degradation, and the penetration of lymphocytes, macrophages, and neutrophils to the joint cavity.…”
Section: Discussionmentioning
confidence: 97%
“…In both models, the compound diminished the edema [19]. Hawtriwaic acid at doses of 5, 10, and 20 mg/kg decreased knee inflammation in a murine model of monoarthritis induced with kaolin/carrageenan, by the reduction of serum levels of the pro-inflammatory interleukins Il-1β, IL-6, and TNF-α, and the increase in the serum levels of the anti-inflammatory interleukin IL-10 [20]. Ursolic acid, a pentacyclic triterpene found in many plant species, was identified for the first time in 1920 in the epicuticular waxes of apples.…”
Section: Terpenesmentioning
confidence: 96%
“…The use of substances able to induce anti-inflammatory or reduce proinflammatory cytokines can represent an important advance in the therapeutic treatment of a range of diseases. In this respect, terpenes stand out as an interesting option for the discovery of new bioactive molecules for arthritis injury, especially as an alternative to reduce the inflammatory process (Barreto et al, 2016, Brito et al, 2015, de Santana Souza et al, 2014, Salinas-Sánchez et al, 2015 . Our review highlighted 14 terpenes (Table 1) that are able to modulate the levels of cytokines in different models of arthritic diseases, and thereby contribute to improving the clinical profile by reducing the inflammatory process and pain.…”
Section: Modulate Inflammatory and Anti-inflammatory Cytokinesmentioning
confidence: 99%